Aggressive Low Carbon Innovation (ALCI): A Conceptual Framework for Sustainable Business Competitiveness - Andi Hendra Paluseri; Thomas S. Kaihatu; Timotius Febry Christian (Jurnal Indonesia Sosial Teknologi, 2025)
The transition toward sustainability in business operations has become a critical driver for competitive advantage in the modern economy. This study explores the integration of Green Innovation Capability (GIC) and Strategic Aggressiveness (SA) to develop the Aggressive Low Carbon Innovation (ALCI), a conceptual framework designed to enhance sustainable business competitiveness. The study synthesizes literature insights and expert interviews using qualitative research methodology to construct a model that aligns organizational transformation, operational optimization, and system integration. The ALCI conceptual framework identifies key enablers such as technological adoption, supply chain optimization, leadership commitment, cultural shifts, and effective data management. These components are strategically linked to address challenges like cost of transition, resistance to change, and system integration complexities. The framework emphasizes aggressive, proactive strategies for implementing green initiatives, fostering collaboration across departments, and leveraging innovative technologies to optimize sustainability outcomes. The study contributes to sustainability literature by demonstrating how combining GIC and SA can facilitate organizational transformation and operational efficiency, enabling firms to achieve a green business model. This framework provides practical implications for managers and policymakers seeking to implement robust green strategies that align with corporate sustainability goals and enhance competitive positioning in the global marketplace. Further research is recommended to validate this model across diverse industries and geographic regions.